Specificity, Dose Dependency, and Kinetics of Markers of Chicken and Beef Intake Using Targeted Quantitative LC‐MS/MS: A Human Intervention Trial. Issue 5 (29th January 2020) - Giesbertz, Pieter; Brandl, Beate; Lee, Yu‐Mi; Hauner, Hans; Daniel, Hannelore; Skurk, Thomas
Abstract : Scope: Common methods for food intake assessment are error‐prone. Estimating food intake via metabolite biomarkers in blood/urine is challenged by inter‐individual variation. Here, meat intake markers based on criteria defined within the FoodBAll consortium, including dose dependency, specificity, kinetics, and their ability to predict meat dose, are evaluated. Methods and results: In two randomized human interventions, meat at different doses are consumed. Plasma concentrations of 100 analytes, including previously proposed meat intake markers, are determined at different time points up to 24 h after meat ingestion using targeted liquid chromatography–tandem mass spectrometry. Plasma concentrations of π‐methylhistidine (π‐M‐His) correlated best with the chicken meat amount consumed even after 24 h ( R 2 = 0.96). Both, anserine and π‐M‐His show first‐order elimination kinetics, irrespective of meat dose ( t 1/2 is 1.4 and 5.9 h, respectively). Surprisingly, π‐M‐His best predicted the amount of beef consumed, albeit at lower concentrations. Furthermore, trimethylamine‐ N ‐oxide (TMAO) increases only after beef, while dimethylglycine only after chicken consumption. The lack of baseline concentrations for π‐M‐His and anserine is likely the strength of these compounds to predict meat dose. Conclusion: Quantitative assessment of meat intake within 24 h is most accurate with π‐M‐His, whereas TMAO and dimethylglycine best discriminate between chicken and beef. Abstract : An intervention with chicken and beef is performed to evaluate meat markers. Dose dependency, specificity, kinetics, and predictive power of known and novel markers are analyzed. π‐Methylhistidine best predicted dose for both chicken and beef. Anserine and π‐methylhistidine also discriminated the meat types, as values after chicken intake are much larger. In opposition to this, trimethylamine‐ N ‐oxide increases only after beef intake.